Hydrogel-Based Cell Therapies for Kidney Regeneration: Current Trends in Biofabrication and In Vivo Repair - Jansen, Katja; C.L. Schuurmans, Carl; Jansen, Jitske; Masereeuw, Rosalinde; Vermonden, Tina (Current Pharmaceutical Design, 2017)
Facing the problems of limited renal regeneration capacity and the persistent shortage of donor kidneys, dialysis remains the only treatment option for many end-stage renal disease patients. Unfortunately, dialysis is only a medium-term solution because large and protein-bound uremic solutes are not efficiently cleared from the body and lead to disease progression over time. Current strategies for improved renal replacement therapies (RRTs) range from whole organ engineering to biofabrication of renal assist devices and biological injectables for in vivo regeneration. Notably, all approaches coincide with the incorporation of cellular components and biomimetic micro-environments. Concerning the latter, hydrogels form promising materials as scaffolds and cell carrier systems due to the demonstrated biocompatibility of most natural hydrogels, tunable biochemical and mechanical properties, and various application possibilities. In this review, the potential of hydrogel-based cell therapies for kidney regeneration is discussed. First, we provide an overview of current trends in the development of RRTs and in vivo regeneration options, before examining the possible roles of hydrogels within these fields. We discuss major application-specific hydrogel design criteria and, subsequently, assess the potential of emergent biofabrication technologies, such as micromolding, microfluidics and electrodeposition for the development of new RRTs and injectable stem cell therapies.
Keywords: hydrogels